Efficient Organocatalyst Supported on a Simple Ionic Liquid as a Recoverable System for the Asymmetric Diels–Alder Reaction in the Presence of Water. Issue 5 (28th January 2015) - De Nino, Antonio; Maiuolo, Loredana; Merino, Pedro; Nardi, Monica; Procopio, Antonio; Roca‐López, David; Russo, Beatrice; Algieri, Vincenzo
Abstract The synthesis, characterization, and evaluation of a new highly efficient organocatalyst, namely, (5S)‐2, 2, 3‐trimethyl‐5‐thiobenzylmethyl‐4‐imidazolidinone hydrochloride, has been achieved. The catalyst possesses important structural features that should increase the catalytic efficiency and solubility in polar media. The application of the ionic‐liquid‐supported imidazolidinone catalyst in enantioselective Diels–Alder reactions was investigated. The Diels–Alder reactions of several dienes and dienophiles proceeded efficiently in the presence of the catalyst to provide the desired products in moderate to good yields and from good to excellent enantioselectivities. The conformation study confirms that in the transition state the Re face is shielded completely by the phenyl ring and an approach on the less hindered Si face is preferred. Particularly remarkable is the fact that the entire ionic liquid/HCl 0.01 M/catalyst system can be recovered and reused in up to six runs without an appreciable loss of catalytic activity.